The Analytical Solutions for Stochastic Fractional-Space Burgers’ Equation - Farah M. Al-Askar; Wael W. Mohammed; M. El-Morshedy (Journal of Mathematics)
We consider here the stochastic fractional-space Burgers’ equation (SFSBs’E) forced by multiplicative noise. Our goal in this paper is to find the analytical solutions for SFSBs’E via the G′/G-expansion method. Also, we generalize some previously results where this equation was not studied before with fractional space and multiplicative noise in the itô sense. Moreover, we utilize graphical representations to discuss the effect of the stochastic term on the stability of the SFSBs’E solutions.